Instruments of Cognizing the Social and Economic Field of Society: Objectives, Challenges and Prospects - N. P. Tishkina; G. A. Rybina (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
Today’s concepts, theories and methodology of classical political economy, economics in general, state and economic governance clearly demonstrate their unsoundness in resolving issues of rational organization of public reproduction by levels of economic management. They are characterized by the subjective-contract and dogmatic tool and the relevant theory of cognition, which are aimed at retaining the discriminative-degrading, religiouspolitical initial model of man and society vital functions in nature, i. e. ‘Tyrant – Victim’. Their alternative is the system-integrated inter-disciplinary methodology providing the development of scientific, objective economic theory, rational practice of state and economic governance of public production, which excludes political mongering, subjectivism and voluntarism. The current internal and external situation in Russia shows that neither traditional public sciences and their leading academics, nor state bodies and their advisers-scientists, nor politicians can produce a variant of further positive development of society and production for the near future. An additional set of notions, categories and tools of cognition supplementary to the traditional one was designed on the basis of approaches put forward by supporters of classical political-economic, biosphere, noosphere and fundamental sciences. It does not reject the accumulated experience, which can be adapted, concretize and correct to improve the quality of research in accordance with the extended totality of objective general, social and economic laws of man and society development in nature.